The relationship between athletic mental energy and eating behaviors - Yıldız, Aydıner Birsin; Algün Doğu, Gözde; Parlakkılıç Büyükakgül, Seniz; Yaman Yılmaz, Ceren (Progress in Nutrition, 2020)
Study Objectives: The study aimed to contribute to the research and understanding of the concept of athletic mental energy (AME), which seems to be lacking in the literature. For this purpose, the relationship between athletic mental energy and eating habits was examined in a sample of professional football players. Methods: A total of 254 professional men football players with a mean age of 24.22±4.62 years, mean of 11.50±4.50 sports ages, participated in the study. The research used The Three - Factor Eating Questionnaire (TFEQ-R18) and The Athletic Mental Energy Scale (AMES). TFEQ-R18 was developed by Karlson et al (2000) and adapted to Turkish by Kıraç et al (2015). AMES was developed by Lu et al (2018) and adapted to Turkish by Yıldız et al (2020). Descriptive statistics and Simple Linear Regression Analysis methods were used in the analysis of the data obtained. The analyzes were made in the SPSS 22 package program and the significance level was taken as p <0.05 in all analyzes in the study. Results: As the result of research, it has been determined that cognitive restraint is positively correlated with AME, uncontrolled eating is negatively correlated with AME, emotional eating is negatively correlated with AME and susceptibility to hunger is negatively correlated with AME. Conclusion: We can state that eating behavior are predictors of cognitive energy as a result of research.